Predicting the development of in-hospital cardiogenic shock in patients with ST-segment elevation myocardial infarction treated by primary percutaneous coronary intervention: the ORBI risk score. (15th March 2018) - Auffret, Vincent; Cottin, Yves; Leurent, Guillaume; Gilard, Martine; Beer, Jean-Claude; Zabalawi, Amer; Chagué, Frédéric; Filippi, Emanuelle; Brunet, Damien; Hacot, Jean-Philippe; Brunel, Philippe; Mejri, Mourad; et al.
Abstract: Aims: To derive and validate a readily useable risk score to identify patients at high-risk of in-hospital ST-segment elevation myocardial infarction (STEMI)-related cardiogenic shock (CS). Methods and results: In all, 6838 patients without CS on admission and treated by primary percutaneous coronary intervention (pPCI), included in the Observatoire Régional Breton sur l'Infarctus (ORBI), served as a derivation cohort, and 2208 patients included in the obseRvatoire des Infarctus de Côte-d'Or (RICO) constituted the external validation cohort. Stepwise multivariable logistic regression was used to build the score. Eleven variables were independently associated with the development of in-hospital CS: age >70 years, prior stroke/transient ischaemic attack, cardiac arrest upon admission, anterior STEMI, first medical contact-to-pPCI delay >90 min, Killip class, heart rate >90/min, a combination of systolic blood pressure <125 mmHg and pulse pressure <45 mmHg, glycaemia >10 mmol/L, culprit lesion of the left main coronary artery, and post-pPCI thrombolysis in myocardial infarction flow grade <3. The score derived from these variables allowed the classification of patients into four risk categories: low (0–7), low-to-intermediate (8–10), intermediate-to-high (11–12), and high (≥13). Observed in-hospital CS rates were 1.3%, 6.6%, 11.7%, and 31.8%, across the four risk categories, respectively. Validation in the RICO cohort demonstrated in-hospital CS rates of 3.1% (score 0–7), 10.6% (score 8–10), 18.1% (score 11–12), and 34.1% (score ≥13). The score demonstrated high discrimination (c-statistic of 0.84 in the derivation cohort, 0.80 in the validation cohort) and adequate calibration in both cohorts. Conclusion: The ORBI risk score provides a readily useable and efficient tool to identify patients at high-risk of developing CS during hospitalization following STEMI, which may aid in further risk-stratification and thus potentially facilitate pre-emptive clinical decision making.